2013
DOI: 10.1080/10503307.2013.838653
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory study of the relationship between changes in emotion and cognitive processes and treatment outcome in borderline personality disorder

Abstract: This exploratory study examined specific emotion processes and cognitive problem-solving processes in individuals with borderline personality disorder (BPD), and assessed the relationship of these changes to treatment outcome. Emotion and cognitive problem-solving processes were assessed using the Toronto Alexithymia Scale, the Linguistic Inquiry Word Count, the Derogatis Affect Balance Scale, and the Problem Solving Inventory. Participants who showed greater improvements in affect balance, problem solving, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 75 publications
2
46
0
2
Order By: Relevance
“…Higher levels of inhibitory affects (e.g., shame, guilt, or pain) were associated with a less adaptive self-image. Moreover, preliminary evidence supports the theory that specific improvements in emotion processes are associated with positive long-term treatment outcomes, such as reduced symptom distress and improved interpersonal functioning, in patients with BPD, as well as in patients with depression in a mixed clinical sample (Herrmann, Greenberg, & Auszra, 2014;McMain et al, 2013;Pos & Greenberg, 2012). Taken together, cross-sectional and prospective research using different conceptual tools suggests that emotional awareness, tolerance, and expressivity may be related to levels of personality functioning in both self and relational areas.…”
mentioning
confidence: 57%
“…Higher levels of inhibitory affects (e.g., shame, guilt, or pain) were associated with a less adaptive self-image. Moreover, preliminary evidence supports the theory that specific improvements in emotion processes are associated with positive long-term treatment outcomes, such as reduced symptom distress and improved interpersonal functioning, in patients with BPD, as well as in patients with depression in a mixed clinical sample (Herrmann, Greenberg, & Auszra, 2014;McMain et al, 2013;Pos & Greenberg, 2012). Taken together, cross-sectional and prospective research using different conceptual tools suggests that emotional awareness, tolerance, and expressivity may be related to levels of personality functioning in both self and relational areas.…”
mentioning
confidence: 57%
“…Patients with BPD can be grouped very differently according to the categorical diagnostic criteria taken into account. These groups constitute very different clinical sub-categories, which also had varied response to treatment (Critchfield et al, 2008;McMain et al, 2013). It is plausible that such clinical sub-categories present also different profiles of mindreading impairments, which have not been considered in this study.…”
Section: Discussionmentioning
confidence: 90%
“…A Canadian study found evidence for improvements in affect balance, problem‐solving associated with greater reductions in general symptom distress and greater improvements in interpersonal functioning when people with a diagnosis of BPD were given more information about BPD (McMain et al . ). This highlights the importance of health literacy and self‐management strategies.…”
Section: Discussionmentioning
confidence: 97%